Management : a sourcebook - Thomson, Murna (The Dunmore Press, 1989)
This book is about managing large and small organisations, particularly in the South Pacific. Drawing on research trends and contemporary analytical frameworks, its fourteen contributors outline and discuss key elements in the Management Process and how they are affected by Organisational Behaviour and Design. Examples from business and other organisations and the consulting experiences of the authors are used throughout. Most significantly, the book integrates and summarises a wealth of research information about organisations and their management, and shows how it relates to questions and issues facing today's managers.